2020
DOI: 10.1007/s00432-020-03382-9
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic effects of targeting CCR5 and its therapeutic potential for colorectal cancer liver metastasis

Abstract: Purpose Liver metastasis is observed in up to 50% of colorectal cancer (CRC) patients. Available treatment options are limited and disease recurrence is often. Chemokine receptor 5 (CCR5) has attracted attention as novel therapeutic target for treating cancers. In this study, we reinforced the importance of CCR5 as therapeutic target in CRC and its liver metastasis by applying in vitro, in vivo and clinical investigations. Methods By targeting CCR5 via siRNAs or an FDA approved antagonist (maraviroc), we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Thus, cyclin D1 and cyclin E1 are in moderate higher activity to activate CDK4/6/2 and promote G1/S phase of cell cycle. 127 , 128 …”
Section: Ccl5/ccr5 and Diseasesmentioning
confidence: 99%
“…Thus, cyclin D1 and cyclin E1 are in moderate higher activity to activate CDK4/6/2 and promote G1/S phase of cell cycle. 127 , 128 …”
Section: Ccl5/ccr5 and Diseasesmentioning
confidence: 99%
“…miR-125a-3p harbored a negative correlation with circ_0002483 expression, repressed cell proliferation and reversed circ_0002483-induced tumor-promoting effects. In addition, CCL4-CCR5 axis contributes to breast cancer metastasis [ 36 ] and targeting CCR5 inhibits colorectal cancer liver metastasis [ 37 ]. We herein identified that CCL4 was upregulated in LUAC tissues and regarded as a direct target of miR-125a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several reports associate CCR5/CCL5 intermediate or strong expression to extended CRC patient survival as well as tumor regression [31,32], but other studies show that this chemokine receptor significantly contributes to tumor growth through its main actors CCL5, CCL4 and CCL3 [11,16,19,29], and that neutralization of this receptor's chemokines can reduce tumor invasion in colorectal [21,23], breast [33,34] and lung cancers [35,36]. For CRC treatment, CCR5 is widely studied, given its involvement in cancer progression and metastasis, and is a frequently inhibited using specific molecules to hinder the interaction between mesenchymal stem cells (MSC)/CRC cells and to effectively treat CRC advanced stages [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies similar to ours and in different cancer types (colorectal, breast, lung) have demonstrated that overexpression of a functional CCR5 is heavily involved in chemotaxis and immune cells' recruitment to the tumor dissemination site, highlighting a chemokine-receptors protumor effect [22,53]. They demonstrate through in vitro or in vivo experiments that targeting CCR5 via siRNA (second RNA interference) or an FDA (Food and Drug Administration)-approved antagonist (maraviroc), hinders the receptor's biological activity and can be an effective therapy for treating CRC and liver metastasis [21,23,38]. The chemokine-receptor complex molecular interactions seem to be in favor of the immune system and consequently tumor cell elimination [30,31], but CCL5 [16,23], CCL3 [10,15,29] and CCL4 [11,14,15] overexpression, by different cells as well as tumors cells in the tumor microenvironment, exhibit protumor properties [30].…”
Section: Discussionmentioning
confidence: 99%